2013
DOI: 10.1074/jbc.m112.438465
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Transcription and Replication by a Newly Identified Cyclin T1 Splice Variant

Abstract: Background: Production of full-length HIV-1 mRNA requires interaction of cyclin T1 and cyclin-dependent kinase 9 (CDK9) with HIV-1 TAT protein.Results: An inhibitory cyclin T1 splice variant was identified. Conclusion: The newly identified cyclin T1 splice variant inhibits HIV-1 gene transcription. Significance: These new findings may provide new clues for the development of anti-HIV strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Two Cyclin T1 splice variants, namely CycT1a and CycT1b, were reported and play contrary roles in transcription elongation [Gao et al, 2013].The ratio of CycT1b and CycT1a in the cells might be a mark of general transcription activation or suppression. CycT1b is generated by exon skipping of its exon 7, and thus could be specifically amplified by the primer targeting the exon junction of exon 6 and 8 ( CycT1b by semi-quantitative RT-PCR (Fig.…”
Section: Results: Screening For Splicing Factors Targeting the Gene Fmentioning
confidence: 99%
See 4 more Smart Citations
“…Two Cyclin T1 splice variants, namely CycT1a and CycT1b, were reported and play contrary roles in transcription elongation [Gao et al, 2013].The ratio of CycT1b and CycT1a in the cells might be a mark of general transcription activation or suppression. CycT1b is generated by exon skipping of its exon 7, and thus could be specifically amplified by the primer targeting the exon junction of exon 6 and 8 ( CycT1b by semi-quantitative RT-PCR (Fig.…”
Section: Results: Screening For Splicing Factors Targeting the Gene Fmentioning
confidence: 99%
“…On the other hand, the role of CycT1b in the regulation of gene transcription remains to be elucidated. Data from our previous work suggested that CycT1b might negatively regulate the transcription of certain cellular genes [Gao et al, 2013].…”
Section: Cyct1-dependent Cellular Genesmentioning
confidence: 96%
See 3 more Smart Citations